Design and development of high voltage high frequency power supply for water treeing analysis - 392229 Goh, Leep Sean (Skudai : Universiti Teknologi Malaysia, 2001)
Project Paper (Bachelor of Electrical Engineering) - Universiti Teknologi Malaysia, 2001